Hydrodynamic Characteristics Study of Bionic Dolphin Tail Fin Based on Bidirectional Fluid–Structure Interaction Simulation - Ning Wang; Yu Zhang; Linghui Peng; Wenchuan Zhao (Biomimetics)
Using bidirectional fluid–structure interaction technology, the dorsal–ventral motion of the dolphin tail fin was simulated, and the feasibility of the numerical simulation method was validated through underwater motion experiments. This study investigated the effects of structural parameters and motion modes of bionic dolphin tail fins on their propulsion performance. The results show that flexible tail fins can enhance propulsion performance. Compared to equal-thickness flexible tail fins, variable-thickness flexible tail fins that conform to the structural characteristics of real dolphin tail fins exhibit better propulsion performance. Asymmetric motion modes have a certain thrust-enhancing effect, but altering the frequency ratio <semantics>F</semantics> and amplitude ratio <semantics>H</semantics> of heaving motion leads to an increase in pitching moment, reducing swimming stability. Additionally, the greater the difference in frequency and amplitude between the up-and-down motions, the larger the pitching moment. The study results provide references for the optimized design and motion control of bionic tail fins.